Cooling system for kampung house - Paul Marcos, Aeron (Universiti Malaysia Sarawak, UNIMAS, 2010)
In Malaysia, installing heat insulator at the attic region is not practical in kampung area. This study is carried out to determine the reliability of heat insulator to decrease the heat gain in kampung house. Besides that, the study test lokan shell fiber composite as heat insulator material and to compare its performance with other heat insulator as gypsum board, polystyrene and asbestos. Lokan or to be specific, the family of freshwater mussels and the species known as “Polymesoda Expansa” or in the local dialect recognized it as “lokan”. This study also determines the effect of attic air space ventilation in decreasing the interior region heat gain by the cell. For this study five identical test cell were used. Four of it were installed with different insulator including lokan composite, the remaining cell were used as a reference. Analysis of result shows that lokan composite was comparable to asbestos and polystyrene performance in the non-ventilated attic region. When attic region is ventilated, lokan composite shows a better performance than any other insulator tested.